Teaching Writing in the Midst of Fragile Alliances: Insights from Literacy Teacher Educators. (1st October 2020) - Smith, Patriann; Varner, Jessica; Nigam, Anita; Liu, Yilan; Lesley, Mellinee; Smit, Julie; Burke, Dawn; Beach, Whitney
ABSTRACT: The purpose of this phenomenological narrative study was to describe what it means to be Literacy Teacher Educators (LTEs) who supported writing in the context of a research–practice partnership (RPP) in the southwestern United States and to identify elements of the RPP in which we worked that were most useful for supporting writing instruction in "underperforming" schools. Inductive analyses of five literacy teacher educators' 12 phenomenological interviews revealed that LTEs were university-school liaisons who: a) used our intertwined identities as LTEs and as writers to understand how to provide support; (b) served as advocates for culturally and lingusitically diverse students (CLDs); (c) used our advocacy for students to determine how to leverage administrative support for writing; and (d) navigated the structural expectations of our roles across the university and schools by focusing more on encouragement than critique in supporting teachers. Elements of the RPP most useful for supporting writing instruction were: (a) LTE understanding; (b) RPP structure; (c) teacher follow-through; (d) improved writing results; and (e) the use of real-life experiences for students. Implications for teachers and administrators who support writing in schools are provided.